Non-linear associations of serum spermidine with type 2 diabetes mellitus and fasting plasma glucose: a cross-sectional study - Zhang, Xiaohong; Zhang, Yao; Li, Shaojie; Liu, Min; Lu, Ying; He, Mengyao; Sun, Zhaoqing; Ma, Mingfeng; Zheng, Liqiang (Frontiers in Nutrition, 2024)
Background Previous animal experiments have demonstrated the potential of spermidine to mitigate glucose intolerance, insulin resistance, and hyperinsulinemia. However, there remains a scarcity of epidemiological evidence supporting these findings. Therefore, we aimed to elucidate the associations of serum spermidine with T2DM and FPG. Materials and methods The cross-sectional study was conducted from June to August 2019 in the rural areas of Fuxin County, Liaoning Province, China. A total of 4,437 participants were included in the study. The serum spermidine was detected using high-performance liquid chromatography with a fluorescence detector. FPG was measured using the hexokinase method. T2DM was defined as participants with a FPG level of 7.0 mmol/L or greater, or self-reported diagnosis of diabetes by a doctor. Restricted cubic spline model and piecewise linear regression model were used to explore the associations of serum spermidine with T2DM and FPG, respectively. Results The mean (SD) age of the participants was 59.3 (10.0) years, with 622 out of 4,437 participants being defined as T2DM. The serum spermidine in participants stratified by age and BMI categories was significantly different, with p values of 0.006 and 0.001, respectively. Among all the participants, the association of serum spermidine with T2DM was J-shaped. The log (spermidine) was negatively associated with T2DM (OR = 0.68, 95% CI: 0.52 to 0.92, p = 0.01) below the inflection point, while log (spermidine) was not significantly associated with T2DM (OR = 1.97, 95% CI: 0.93 to 4.15, p = 0.07) above the inflection point. Among the participants without T2DM, the association of serum spermidine with FPG was inverted J-shaped. The log (spermidine) was positively associated with FPG (β = 0.13, 95% CI: 0.05 to 0.21, p = 0.001) below the inflection point, while log (spermidine) was negatively associated with FPG (β = −0.29, 95% CI: −0.42 to −0.16, p < 0.001) above the inflection point. Conclusion In conclusion, non-linear associations of serum spermidine with T2DM and FPG were found in the cross-sectional study in Chinese rural adults. This provided insights into the use of spermidine for the prevention of T2DM, highlighting the potential role in public health prevention strategies of spermidine.